2012
DOI: 10.1080/02791072.2012.703510
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stigmatization Towards Use of Various Illicit Drugs Among Emerging Adults

Abstract: The stigma associated with illegal drug use is nearly universal, but each drug is associated with its own specific level of stigma. This study examined level of stigmatization towards users of various illegal drugs and determined what variables explain such attitudes. A sample of emerging adults (age 18 to 25) was surveyed throughout New York City (N = 1021) and lifetime use, level of exposure to users, and level of stigmatization was assessed regarding use of marijuana, powder cocaine, Ecstasy, and nonmedical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 39 publications
2
33
1
Order By: Relevance
“…In addition, we found that increased frequency of witnessing drug selling was associated with lower levels of friend disapproval toward use of marijuana and cocaine. Disapproval (self-, peer-, and perceived societal disapproval) has previously been found to be a robust protective factor against drug use [34,37,57-60]. These findings suggest that increased frequency of witnessing drug selling in one’s neighborhood is associated with lowered friend disapproval toward marijuana, but much higher frequency of witnessing drug selling was needed in order for students to report significantly lower friend disapproval toward cocaine.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, we found that increased frequency of witnessing drug selling was associated with lower levels of friend disapproval toward use of marijuana and cocaine. Disapproval (self-, peer-, and perceived societal disapproval) has previously been found to be a robust protective factor against drug use [34,37,57-60]. These findings suggest that increased frequency of witnessing drug selling in one’s neighborhood is associated with lowered friend disapproval toward marijuana, but much higher frequency of witnessing drug selling was needed in order for students to report significantly lower friend disapproval toward cocaine.…”
Section: Discussionmentioning
confidence: 75%
“…Importantly, sociological and psychological theories, such as Social Norms Theory [35] and the Theory of Planned Behavior [36], suggest that neighborhood illicit drug selling could be associated with peer illicit drug disapproval. In addition, disapproval and stigmatization towards illicit drug use has previously been shown to be an important correlate of illicit drug use [37]. Research on how perceived neighborhood drug selling relates to both use and (peer) attitudes towards use would add to the literature as there is a lack of information whether perception of neighborhood drug selling is a risk factor for use.…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, there may be lesser degree of realization that the prescription opioid users are in-fact substance users, and are not taking the opioids for medical complaints. Lastly, it is possible that users of illicit drugs appraise stigma towards substance use differently when compared to users to legal substances (Palamar et al 2012). All of the above reasons may contribute to greater experienced stigma reported by alcohol users.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma perceived towards substance users was similar across the patients and their family members for both alcohol-and opioid-dependent groups in the present study. Previous literature suggests that substance Stigma Towards Substance Use in India 5 users might have less stigmatizing attitudes towards illicit ubstance use than nonusers (Palamar, Kiang & Halkitis, 2012). On the other hand, there is some evidence that substance users might have more stigmatizing views towards other substance users (Sorsdahl, Stein, & Myers, 2012).…”
Section: Discussionmentioning
confidence: 99%